Analisis Pelayanan Digital Minimarket di Politeknik Negeri Bandung Terhadap Kepuasan Mahasiswa - Yona Agustin (International Journal Administration, Business & Organization, 2022)
The aim of this research is to investigate the impact of digital minimarket services on the satisfaction of students at the Bandung State Polytechnic, Indonesia. The study involves 112 respondents as participants. It employs a quantitative descriptive method with descriptive analysis and data analysis using correlation and regression methods. Data collection is conducted through questionnaires distributed via social media and face-to-face interactions with respondents. The research findings indicate that digital minimarket services at the Bandung State Polytechnic have a very strong influence on student satisfaction, suggesting that these services contribute significantly to enhancing student satisfaction.